The Impact of Work-Life Balance and Work Stress on Turnover Intention in Millennial Generation - Ahmad Suhail Kusnadi; Gusti Wiliandi; Lisa Harry Sulistyowati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study reveals that the influence of work-life balance and Job Stress on Turnover Intention among the millennial generation Study on millennial generation workers in Kuningan district, which has a significant influence on the level of turnover intention in millennial generation workers. High levels of stress in the workplace have been shown to contribute to an increase in employee intention to resign, factors such as heavy work pressure, a less supportive work environment, and high job demands are the main triggers for increased stress, which in turn encourages employees to look for other job alternatives. This research uses quantitative methods. The research population used was millennial generation workers in Kuningan Regency. The purposive sampling technique was used to determine a sample of 127 respondents who work in manufacturing companies in brass district. Using Google Forms, data was collected from millennial workers in Kuningan Regency aged between 25 and 40 years. The results showed that there was a significant influence between Based on the results of the F test, a significance value of 0.000 (α < 0.05) was obtained. So it can be concluded that the variables Impact work life balance (X1) and Work Stress (X2) simultaneously have a significant effect on the Turnover Intention (Y) variable.